2021
DOI: 10.1111/jch.14342
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of nighttime home blood pressure measured by a wrist‐type nocturnal home blood pressure monitoring device

Abstract: The authors investigated the reproducibility of nighttime home blood pressure (BP) measured by a wrist‐type BP monitoring device. Forty‐six hypertensive patients (mean 69.0±11.6 years, 56.5% male) self‐measured their nighttime BP hourly using simultaneously worn wrist‐type and upper arm‐type nocturnal home BP monitoring devices at home on two consecutive nights. Using the average 7.4±1.3 measurements on the first night and the average 7.0 ± 1.8 measurements on the second night, the authors assessed the reliabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…However, the “change in BP” had similar BP values and SDs for the brachial and the wrist devices (SBP/DBP at EOT, −12.9 ± 10.3/−5.4 ± 5.6 for the brachial, and −11.7 ± 10.9/−5.4 ± 6.0 for the wrist). As previously reported [ 4 7 ], these results suggest that the wrist device can be used to monitor nighttime BP changes as well as the brachial type recommended in the guidelines. Advances in the development of HBPM devices reduce patients’ burdens, and enable them to monitor nighttime BP, which has been previously only measurable by ABPM.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…However, the “change in BP” had similar BP values and SDs for the brachial and the wrist devices (SBP/DBP at EOT, −12.9 ± 10.3/−5.4 ± 5.6 for the brachial, and −11.7 ± 10.9/−5.4 ± 6.0 for the wrist). As previously reported [ 4 7 ], these results suggest that the wrist device can be used to monitor nighttime BP changes as well as the brachial type recommended in the guidelines. Advances in the development of HBPM devices reduce patients’ burdens, and enable them to monitor nighttime BP, which has been previously only measurable by ABPM.…”
Section: Discussionsupporting
confidence: 83%
“…Identifying patients with nocturnal hypertension is difficult because of the high patient burden of measuring nighttime blood pressure (BP) with ambulatory BP monitoring (ABPM). However, recent development of brachial and wrist type nocturnal home BP monitoring (HBPM) devices makes taking nighttime BP measurements easier [ 2 , 4 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the correlation between the two HBPM devices, previous reports have shown that nighttime home BP measurements obtained with the wrist device are reproducible and were consistent with measurements obtained with the brachial device 28–30 . However, their correlation before and after administration of antihypertensive drugs had not been investigated previously.…”
Section: Discussionmentioning
confidence: 75%
“…Correlation between brachial and wrist HBPM devices for measuring nighttime home SBP at baseline (A), week 12 (B), and change from baseline to week 12 (C). HBPM, home blood pressure monitoring; SBP, systolic blood pressure.Regarding the correlation between the two HBPM devices, previous reports have shown that nighttime home BP measurements obtained with the wrist device are reproducible and were consistent with measurements obtained with the brachial device [28][29][30]. However, their correlation before and after administration of antihypertensive drugs had not been investigated previously.…”
mentioning
confidence: 76%
“…Office BP does not allow the detection of any of these conditions, as they can only be diagnosed by ABPM or HBPM and especially the former since home BP monitors that can be programmed to perform measurements during sleep exist but are not very widely used [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%